THE THE CONSTRUCTION OF WOMEN'S FAULTS IN THE NARRATIVE OF THE FRUIT OF KHULDI: A TEXTUAL ANALYSIS OF THE QUR'AN AND TAFSIR TRADITION - Aprilia Musawamah; Ade Jaya Suryani; Muhammad Afif; Ade Fakih Kurniawan (Institut Agama Islam Negeri (IAIN) Curup, 2026)
In general, popular narratives often portray Eve as the main cause of humanity's fall. However, a textual reading of the Qur'anic verses shows that Adam and Eve are depicted as collective subjects in the act of transgression, while the primary source of temptation is explicitly attributed to Satan. This study aims to examine the construction of female fault in the narrative of the forbidden fruit by tracing the differences between the Qur'anic text and the development of its interpretation in religious tradition. This study uses a qualitative approach with library research methods, through content analysis and a critical-hermeneutic approach to the Qur'anic verses as well as classical and contemporary exegesis works. The research results indicate that the construction of women's errors does not originate from the text of the Qur'an, but is formed through a historical process involving the incorporation of Isrā’īliyyāt narratives, reproduction within exegetical traditions, and the influence of a patriarchal socio-cultural context. Therefore, it is very important to engage in a comprehensive analysis of religious texts, taking into account the socio-cultural context in which they were produced, to prevent the perpetuation of deep-rooted gender bias that can distort our understanding of sacred writings. This approach will facilitate a more balanced and fair interpretation of the narratives surrounding the fruit of the khuldi, allowing it to be appreciated as a profound illustration of the collective moral obligations inherent to human experience across diverse cultures and traditions.